Occult Kidney Dysfunction in Children With Transfusion-Dependent Thalassemia - Mohd Zikre, Nurwahida; Muhamad, Nor A.; Eng, Caroline S. Y.; Zailanalhuddin, Nur E.; Lai, Charles D.; Foo, Jen C.; Yap, Suet L.; Ariffin, Hany; Abu Bakar, Karmila (Frontiers in Pediatrics, 2021)
Background: Thalassemia is the commonest hemoglobinopathy in South East Asian. Kidney dysfunction is an under-reported sequelae in children with thalassemia. We conducted a retrospective study to identify the prevalence of and predisposing factors for kidney dysfunction in children with transfusion-dependent thalassemia (TDT). Method: Abnormal kidney function was defined as children with glomerular filtration rate (GFR) of <90ml/min/1.73m2 or a decline in GFR of >20ml/min/1.73m2 or presence of nephrotic range proteinuria within 3 years of commencing regular (every < 6 weeks) red cell transfusion. Data analyzed were age at diagnosis of thalassemia, number of transfusion-years, iron chelation therapy, serum ferritin and pre-transfusion hemoglobin levels. Results: Eighty-one children were studied. Mean age was 11.72 ± 5.275 years. Thirty out of 81 (37%) demonstrated abnormal kidney function. Evidence of glomerular hyperfiltration was seen in 29/81 patients (25.85%) at their last clinic visit. This fraction was doubled [48/81 (59.3%)] when the cohort was tracked back by 3 years from the last clinic encounter. Age at diagnosis (RR, 1.157; 95% CI, 1.014–1.319; p = 0.03) and duration of receiving transfusions (RR, 0.984; 95% CI, 0.974–0.994; p = 0.001) were associated with increased risk of developing abnormal kidney function. Conclusion: Abnormal kidney function in children with TDT may be overlooked by medical personnel without active screening measures. Children receiving regular red cell transfusions require systematic surveillance to enable early detection of kidney dysfunction and timely implementation of appropriate therapeutic interventions.